Selected Issues Concerning Monetary Policy and Institutional Design for Central Banks : A Review of Theories - Beddies, Christian (IMF Working Papers; Working Paper ;, 2000)
In the past decades, much work has been geared toward solving the problem of time inconsistency in monetary policy and analyzing the coordination problem between fiscal and monetary policy. This paper provides a review of the theoretical background to these theories, while also focusing on their inherent problems. It concludes that while the literature makes a strong case for central bank independence, more work should be done in the area of determining the desirable degree of independence with a view to the interplay between fiscal and monetary policy.